High annual surgeon volume reduces the risk of adverse events following primary total hip arthroplasty: a registry-based study of 12, 100 cases in Western Sweden. (4th March 2019) - Jolbäck, Per; Rolfson, Ola; Cnudde, Peter; Odin, Daniel; Malchau, Henrik; Lindahl, Hans; Mohaddes, Maziar
Abstract : Background and purpose — Most earlier publications investigating whether annual surgeon volume is associated with lower levels of adverse events (AE), reoperations, and mortality are based on patient cohorts from North America. There is also a lack of adjustment for important confounders in these studies. Therefore, we investigated whether higher annual surgeon volume is associated with a lower risk of adverse events and mortality within 90 days following primary total hip arthroplasty (THA). Patients and methods — We collected information on primary total hip arthroplasties (THA) performed between 2007 and 2016 from 10 hospitals in Western Sweden. These data were linked with the Swedish Hip Arthroplasty Register and a regional patient register. We used logistic regression (simple and multiple) adjusted for age, sex, comorbidities, BMI, fiation technique, diagnosis, surgical approach, time in practice as orthopedic specialist and annual volume. Annual surgeon volume was calculated as the number of primary THAs the operating surgeon had performed 365 days prior to the index THA. Results — 12, 100 primary THAs, performed due to both primary and secondary osteoarthritis by 268 different surgeons, were identified. The median annual surgeon volume was 23 primary THAs (range 0–82) 365 days prior to the THA of interest and the mean risk of AE within 90 days was 7%. If the annual volume increased by 10 primary THAs in the simple logistic regression the risk of AE decreased by 10% and in the adjusted multiple regression the corresponding number was 8%. The mortality rate in the study was low (0.2%) and we could not find any association between 90-day mortality and annual surgeon volume. Interpretation — High annual surgical activity is associated with a reduced risk of adverse events within 90 days. Based on these findings healthcare providers should consider planning for increased surgeon volume.